2014
DOI: 10.1016/j.soard.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

High-risk alcohol use after weight loss surgery

Abstract: Background Bariatric or weight loss surgery (WLS) may alter alcohol metabolism resulting in a higher prevalence of problem drinking post-operatively. Few studies distinguish those who report improvements in drinking from those who report worsening behavior after surgery. Objectives To characterize high risk alcohol use before and after WLS and according to surgery type. Setting 2 academic WLS centers in the United States. Methods We interviewed patients before and annually after WLS. High risk alcohol us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 19 publications
2
35
2
8
Order By: Relevance
“…Thus, it is not surprising that regular alcohol consumption pre-operatively increases the likelihood of an alcoholic disease postoperatively. Although Wee et al [144] could show that more than half of the weight loss patients, who reported alcohol abuse before surgery, discontinued high-risk drinking, and 7% of the patients in this study reported new high-risk drinking 1 year after the intervention. Interestingly, the prevalence of alcohol misuse significantly increases in the 2nd year after surgery as demonstrated by King et al [145].…”
Section: Psychological Aspectscontrasting
confidence: 63%
See 1 more Smart Citation
“…Thus, it is not surprising that regular alcohol consumption pre-operatively increases the likelihood of an alcoholic disease postoperatively. Although Wee et al [144] could show that more than half of the weight loss patients, who reported alcohol abuse before surgery, discontinued high-risk drinking, and 7% of the patients in this study reported new high-risk drinking 1 year after the intervention. Interestingly, the prevalence of alcohol misuse significantly increases in the 2nd year after surgery as demonstrated by King et al [145].…”
Section: Psychological Aspectscontrasting
confidence: 63%
“…Besides, several anatomical or physiological changes upon surgery may also contribute to altered alcohol absorption and/or metabolism [143]. The increased risk of alcohol misuse after surgery could also be due to a shift of addictions, wherein alcohol substitutes food as coping mechanism [144]. Obviously, the pattern of alcohol use pre-operatively also play a role in this addiction transfer.…”
Section: Psychological Aspectsmentioning
confidence: 99%
“…On the other hand, more than half of the patients who reported high-risk alcohol consumption before surgery reduced drinking. However, none of these changes were statistically significant, nor did the two surgical techniques differ each other, although there was a trend toward a higher proportion of RYGB patients, compared to gastric banding, that reduced alcohol use at the year 1 follow-up (Wee et al 2014). …”
Section: Bariatric Surgery As a Risk For Audmentioning
confidence: 96%
“…These data could suggest an alleviation of problematic alcohol use post WLS. This finding is similar to that of Wee and colleagues (2014), who reported that over half of WLS patients who reported "high-risk" drinking prior to surgery, no longer did so at 1 and 2 years postsurgery (Wee et al, 2014). However, it is important to interpret these findings within the context of what was reported earlier having a pre-operative AUD was associated with a higher number of drinking days in the past 30.…”
Section: Alcoholsupporting
confidence: 87%